Organisational learning capabilities (OLC) and knowledge performance in academic libraries in Malaysia / Mohd Shamsul Mohd Shoid - Mohd Shoid, Mohd Shamsul (Institute of Graduate Studies, UiTM, 2016)
Organisational learning capabilities (OLC) can be defined as the organisational and managerial characteristics of factors that encourage learning process or facilitate an organisation to learn while knowledge performance can be explained as the ability of individual, group and organisation to understand what they have learned. Various works and research have dealt with the analysis of this construct from different views and perspectives. However, research has shown that there were lack of studies that explored the perceptions and relationships between organisational learning capabilities’ (OLC) dimensions and knowledge performance in academic libraries. This study was set out to capture the perceptions of organisational learning capabilities among librarians and knowledge performance in academic libraries in Malaysia. A research survey method using questionnaire was distributed to 240 librarians in selected university libraries in Malaysia which reflected the study objectives. From the feedback, only 186 (78%) of the questionnaires were returned and usable for further analysis. Quantitative approach was adopted for this study. The statistical analyses included descriptive and inferential statistics. Parametric tests were used to analyse the data…